Bio-inspired materials for nutrient biocapture from wastewater: Microalgal cells immobilized on chitosan-based carriers. (April 2021) - Vasilieva, Svetlana; Lobakova, Elena; Grigoriev, Timofey; Selyakh, Irina; Semenova, Larisa; Chivkunova, Olga; Gotovtsev, Pavel; Antipova, Christina; Zagoskin, Yuri; Scherbakov, Pavel; Lukyanov, Alexander; Lukanina, Ksenia; et al.
Graphical abstract: Highlights: Cross-linked chitosan polymers have high immobilization efficiency of microalgae. Chitosan polymers do not affect growth and photosynthesis of immobilized microalgae. Chitosan polymers have high mechanical and biological stability in wastewater. Chitosan enhances N, P bioremoval efficiency of immobilized microalga Lobosphaera. Chitosan-attached microalgae are prospective for nutrient recovery as biofertilizer. Abstract: The successful application of the cross-linked chitosan-based polymers for microalgae immobilization and biocapture of nutrients is reported for the first time. Highly porous, hydrophilic polymers were obtained by cross-linking of 250 kDa or 600 kDa chitosan with glutaraldehyde. Both cross-linked chitosan polymers were characterized by high microalgae immobilization efficiency and supported the prolonged cultivation of immobilized Lobosphaera sp. IPPAS 2047 cells without impairing their growth and photosynthetic activity. The 600 kDA chitosan-based polymers demonstrated higher mechanical and biological stability during 7 d incubation than those based on the 250 kDa chitosan. The nutrient removal capacity of the chitosan-immobilized Lobosphaera cells was significantly higher as compared to that of the suspended cells. The specific removal rates of inorganic phosphate and nitrate by the suspended microalgae cells cultivated without cross-linked chitosan polymers comprised 0.36 and 0.50 mg mg −1 Chl d −1, while the chitosan-immobilized Lobosphaera cells consumed phosphate and nitrate at rates 6.01 and 0.65 mg mg −1 Chl d −1, respectively. Collectively, the cross-linked chitosan-based polymers were shown to be environment-friendly materials providing the enhancement of nutrients bioremoval from wastewater by immobilized microalgae cells. The nutrient-enriched microalgae biomass immobilized on the biodegradable and non-toxic chitosan carriers can be applied as slow-releasing biofertilizer.